Single-Dose of Testosterone and the MAOA VNTR Polymorphism Influence Emotional and Behavioral Responses in Men During a Non-social Frustration Task - Wagels, Lisa; Votinov, Mikhail; Hüpen, Philippa; Jung, Sonja; Montag, Christian; Habel, Ute (Frontiers in Behavioral Neuroscience, 2020)
Previous studies suggest that testosterone and several neurotransmitters might interactively influence human aggression. The current study aimed to test potential interactions of a genetic variation linked to the catabolism of serotonin, dopamine and norepinephrine and exogenous testosterone on the reaction towards non-social provocation. In total, 146 male participants were genotyped for a prominent polymorphism of the monoamine oxidase A (MAOA) gene resulting in a short and long variant. Participants completed a non-social frustration task after receiving either a testosterone or a placebo gel in a double-blind set-up. Participants performed a non-social frustration task, where they had to direct a virtually moving ball into a barrel by pulling a joystick (neutral block). During a frustration block, the joystick repeatedly did not respond to participants’ reactions thereby causing failed trials to which participants reacted with increased anger and stronger pulling of the joystick. We analyzed the effect of testosterone administration on emotion and behavior in individuals who either carried a low (L) or high (H) activity MAOA variant. Testosterone administration increased provocation-related self-reported anger and abolished the association between trait aggression and joystick deflection in the frustration block. In MAOA-H carriers endogenous testosterone levels at baseline were associated with increased joystick deflection in both blocks. There was, however, no interaction of testosterone administration and genotype. Although preliminary, the results rather indicate independent influences of exogenous testosterone administration and MAOA, but support an interaction of endogenous testosterone levels and MAOA genetics in a frustration task. The administration of testosterone seems to act on the subjective emotional experience in a provoking situation, while endogenous testosterone levels increased pulling impulses only in carriers of the MAOA-H variant.